Chlorinated Polyfluoroalkyl Ether Sulfonic Acids in Matched Maternal, Cord, and Placenta Samples: A Study of Transplacental Transfer - Chen, Fangfang; Yin, Shanshan; Kelly, Barry C; Liu, Weiping (Environmental science & technology, 2017)
Currently, information regarding concentrations of chlorinated polyfluoroalkyl ether sulfonic acids (Cl-PFESAs) in human placenta does not exist. The main objective of this study was to assess the occurrence and distribution of two Cl-PFESAs, 6:2 Cl-PFESA and 8:2 Cl-PFESA, in maternal serum, umbilical cord serum, and placenta to better assess the transport pathways related to human prenatal exposure. The widely studied perfluorooctanesulfonate (PFOS) was studied for comparison. This study was a hospital-based survey involving quantitative determination of Cl-PFESA and PFOS concentrations in maternal serum (n = 32), cord serum (n = 32), and placenta (n = 32) samples from women in Wuhan, China. The results indicate that Cl-PFESAs can efficiently be transported across placenta, with median exposure levels of 0.60 and 0.01 ng/mL for 6:2 Cl-PFESA and 8:2 Cl-PFESA in the cord sera, respectively. Concentrations of the target compounds in maternal sera, cord sera, and placentas decreased in the following order: PFOS > 6:2 Cl-PFESA > 8:2 Cl-PFESA. Similar patterns were observed in maternal sera, cord sera, and placentas for Cl-PFESAs, with concentrations decreasing in the following order: maternal sera > cord sera > placentas. Significant correlations were observed among 6:2 Cl-PFESA, 8:2 Cl-PFESA, and PFOS concentrations in the maternal serum, cord serum, and placenta samples (r > 0.7; p < 0.001). The median value of R CM (ratio of cord serum to maternal serum concentration) of 6:2 Cl-PFESA was 0.403, indicating a relatively high (∼40%) placental transfer efficiency. 8:2 Cl-PFESA was transported across placenta to a greater extent than 6:2 Cl-PFESA was, likely because of its higher hydrophobicity and lower plasma protein binding affinity. To the best of our knowledge, this is the first study to report the occurrence and distribution of 6:2 Cl-PFESA and 8:2 Cl-PFESA in human placenta. The findings improve our understanding of the mechanisms of transplacental transfer and neonatal exposure to these important PFOS alternatives.